Alkyl-chain-separated triphenybenzene - carbazole conjugates and their derived polymers: candidates for sensory, electrical and optical materials - Kaleeswaran, D.; Vishnoi, Pratap; Kumar, Subramani; Chithiravel, Sundaresan; Walawalkar, Mrinalini G.; Krishnamoorthy, Kothandam; Murugavel, Ramaswamy (Chemistry Select, 2016)
Four new triphenylbenzene based carbazoles (THPBCz4, THPBCz6, THPBCz8 and THPBCz10) and polycarbazoles (polyTHPBCz4, polyTHPBCz6, polyTHPBCz8 and polyTHPBCz10), have been synthesized. Photoluminescence spectra of the monomers in dichloromethane exhibit two intense bands at 353 and 369 nm. Two additional bands (410 and 435 nm) are also observed due to intermolecular interactions. These bands are more intense in the case of thin films, indicating stronger pp stacking interactions in the solid state. Due to the extended p-conjugation, the polycarbazoles display two main emission bands (495 and 520 nm) which are red shifted as compared to the monocarbazoles. Due to the presence of emissive platforms such as triarylbenzene and carbazole, both monomers and polymers, function as efficient sensors for the detection of polynitroaromatic analytes (PA, DNT, rho-DNB and m-DNB). The electrochemically polymerized carbazole derivatives showed maximum capacitance of 41 F/g for polyTHPBCz6. The SCLC measurement reveals a maximum mobility of 6 x 10(-6) cm(2)/Vs for polyTHPBCz4 that showed better packing due to flexible alkyl chains that connect the conjugated moieties.

Nanoporous covalent organic framework embedded with Fe/Fe3O4 nanoparticles as air-stable low-density nanomagnets - Kushwaha, Rinku; Kaleeswaran, Dhananjayan; Haldar, Sattwick; Chakraborty, Debanjan; Mullangi, Dinesh; Borah, Aditya; Vinod, Chathakudath P.; Murugavel, Ramaswamy; Vaidhyanathan, Ramanathan (ACS Applied Nano Materials, 2020)
Covalent organic frameworks (COFs) made of light atoms such as H, C, N, and O with a significant void-to-framework ratio are excellent low-density supports for nanoparticles (nPs). Their framework can be precoded with heteroatoms to ensure binding with metallic nanoclusters. With these advantages, if controlled amounts of magnetic nPs are anchored to them, they can yield low-density organic-inorganic nanomagnets. Their organic nature facilitates fusion with bulk materials such as paper/textile to enable bulk composites with well-dispersed low-density magnets, which have potential for defense and next-generation aviation applications. Herein, we have grown small Fe/Fe3O4 nPs (5-18 wt %) inside a COF. Interestingly, 300 mg of this organic-inorganic framework material (containing 50 mg of nPs) can lift a vial of similar to 15,000 mg (300 times heavier). Also, the hydrophobic COF wraps around the Fe/Fe3O4 nanocluster retaining its room-temperature magnetic character even after 1 year, while the naked nPs lose it within a few days because of air oxidation. Bulk composites with paper and polymers have been made using this low-density Fe-COF to demonstrate their processability.
Keywords: air-stable nanomagnets; Covalent organic framework; Fe/Fe3O4 nanoparticles; low-density nanomagnets; magnetic rayon; nanoporous COF